Community Participation in the Conditional Direct Transfer Mechanism of the Bosques Program - Palacios, Grace (2021)
Chirikyacu, Chunchiwi, and Chirik Sacha, located in the San Martin region (Peru), are indigenous communities affiliated with the National Program of Forest Conservation for Climate Change Mitigation. The three communities approved the implementation of the Conditional Direct Transfer Mechanism (TDC, acronym in Spanish) as a financial tool for primary forest conservation. This research characterizes the participation of the beneficiaries from the type of involvement and participation size along the TDC execution, identifying drivers that facilitate and limit the participation of the beneficiaries’ minority.Minorities, as in any society, have access to fewer opportunities. In the three communities, I found larger minority groups (such as women) than others with less population (such as monolingual), as well as gender norms accepted in the communities, which limit the minority groups from personally growing and learning. With the inputs of 86% of the Program’s beneficiary families, I identified a non-complimentary gender system in most of the program’s activities, which is also dominant in the most favored group in the communities.In conclusion, the major minority group can increase the participants size, from the opportunities that allow the gender complementarity current in each community (internal driver) and the gender approach that the Program incorporates (external driver).